ETUDE DE L’EFFET DE L’IRRADIATION UV SUR LES PROPRIETES OPTIQUE ET MORPHOLOGIQUE DU POLYPROPYLENE. - MOUACI, S.; SAIDI, M.; SAIDI-AMROUN, N. (University of Eloued جامعة الوادي, 2018)
The modification of the physico-chemical properties of polymeric materials under various ionizing radiations is an important area of research for both material surface treatment techniques and material endurance. Our study focuses on the effect of UV radiation on the structural properties of polypropylene. The 25 μm thick films were exposed to UV-A and UVC, under air, for different times ranging from 6 to 20 hours. The surface state of the irradiated samples was observed by the polarization optical microscope (POM). The obtained images reveal that the surface is modified after irradiation, showing cracks of different sizes. The optical properties of virgin and irradiated films were investigated by UV-visible spectroscopy. A decrease in the optical gap has been observed, revealing the creation of point defects.
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Polypropylène; UV; gap optique; MOP, Surface.